THE EXPRESSION OF THE CATEGORY OF "RESPECT" THROUGH SPEECH ACTS IN ENGLISH AND UZBEKISTAN FAIRY TALES: A COMPARATIVE-PRAGMATIC ANALYSIS (International Congress on Economics, Management and Business Studies, 2026)
This scientific article analyzes the features of the expression of the category of “respect” through speech acts in English and Uzbek fairy tales based on a comparative-pragmatic approach. In the study, the concept of respect is interpreted not as a static moral sign, but as a speech phenomenon that arises in the process of communication, adapts to the situation and governs the relationship between characters. By analyzing speech acts such as orders, requests, advice, warnings, prayers and refusals in English and Uzbek fairy tales, the author reveals what pragmatic strategies respect is manifested through. The article highlights how respect in fairy tales of both languages differs in the form, tone and contextual interpretation of speech acts based on real texts. The results of the study show that the category of respect is actively formed in fairy tale discourse through speech acts and that this process is directly related to the national speech culture.
Keywords: Category of respect, speech acts, pragmatics, fairy tale discourse, comparative analysis, English fairy tales, Uzbek fairy tales.